If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 = 3x + 6 Reorder the terms: 7 = 6 + 3x Solving 7 = 6 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 7 + -3x = 6 + 3x + -3x Combine like terms: 3x + -3x = 0 7 + -3x = 6 + 0 7 + -3x = 6 Add '-7' to each side of the equation. 7 + -7 + -3x = 6 + -7 Combine like terms: 7 + -7 = 0 0 + -3x = 6 + -7 -3x = 6 + -7 Combine like terms: 6 + -7 = -1 -3x = -1 Divide each side by '-3'. x = 0.3333333333 Simplifying x = 0.3333333333
| 20=4x+20 | | 4/6-2=6 | | 8w+7=31 | | 11(z+2)-3(z-3)=4(2-3)+3(z-1) | | y=14-(5x-8) | | -19=-5x+12 | | -15=-4n+5 | | x^3+12x^2-3x-910=0 | | 10x-91=-107 | | 240-12x+x*x=0 | | 17x-(8x-4)=13 | | 5/6y=-20 | | -3x/8=-3 | | 2(5z+2)-6=88 | | (5x/8y^3)^2 | | x+24.8=48.5 | | 5(5x-1)=100 | | 40-2x=-38 | | 4x+9x-6x=42+7 | | 23=8x-9 | | 8-3n=n+4 | | -15x-60=-120 | | 10r+4=104 | | 0r+4=104 | | x+9=38 | | logx^2=8 | | -4y-6=1-3y | | -4x/5=60 | | -x+-x+-x+2=-x+-x+8 | | c+9=38 | | 3n-8=n+4 | | 19y-9=18y+27 |